Glasfil Polymer Sdn. Bhd. / Muhammad Zahiruddin Sapuan - Sapuan, Muhammad Zahiruddin (Faculty Of Chemical Engineering, 2021)
The students had the opportunity to complete her internship training at Glasfil Polymer Sdn. Bhd. The student managed to gain a wide range of knowledge such The effective way to market the company through social media as well as multimedia and injection molding knowledge. The student also gained knowledge on safety precautions and hazards which are very important in order to avoid any injury during the process of injection molding. The opportunity to undergo the life as employee is very valuable to student as they need to use this experience later. This is because work culture cannot be studied theoretically. This internship program has helped the students to grasp the ethics, work culture, adapting to new environments while contributing to self confidence, improving and strengthen their skills while discipline them. In conclusion, while the company reap many benefits from student as their extra manpower, the student also gain many benefits from them too which helps them in future.